2014
DOI: 10.1523/jneurosci.2581-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Alpha-Synuclein Aggregation in a Mouse Model of Parkinson's Disease

Abstract: Parkinson's disease and dementia with Lewy bodies are associated with abnormal neuronal aggregation of ␣-synuclein. However, the mechanisms of aggregation and their relationship to disease are poorly understood. We developed an in vivo multiphoton imaging paradigm to study ␣-synuclein aggregation in mouse cortex with subcellular resolution. We used a green fluorescent protein-tagged human ␣-synuclein mouse line that has moderate overexpression levels mimicking human disease. Fluorescence recovery after photobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
142
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 80 publications
14
142
0
Order By: Relevance
“…This suggests that KYP-2047 mainly has an effect on soluble aSyn aggregates, with the PK-resistant fraction representing an oligomeric pool acquired before treatment initiation. Cremades et al (2012) showed that PK-resistant aSyn oligomers can be generated in initial stages at physiological concentrations, and PK-resistant species have been observed in presynaptic terminals in both transgenic animals (Tanji et al, 2010;Spinelli et al, 2014) and human disease with LBs, and they propose a mechanism that causes synaptic disturbances that are preceded by overt THϩ neuron loss (Kramer and SchulzSchaeffer, 2007). Our results suggest that AAV-aSyn injection caused an increase in both soluble and insoluble forms of oligomers, while evidence in the literature points to soluble aggregate forms being more toxic than insoluble aggregates (Karpinar et al, 2009;Winner et al, 2011;Rockenstein et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that KYP-2047 mainly has an effect on soluble aSyn aggregates, with the PK-resistant fraction representing an oligomeric pool acquired before treatment initiation. Cremades et al (2012) showed that PK-resistant aSyn oligomers can be generated in initial stages at physiological concentrations, and PK-resistant species have been observed in presynaptic terminals in both transgenic animals (Tanji et al, 2010;Spinelli et al, 2014) and human disease with LBs, and they propose a mechanism that causes synaptic disturbances that are preceded by overt THϩ neuron loss (Kramer and SchulzSchaeffer, 2007). Our results suggest that AAV-aSyn injection caused an increase in both soluble and insoluble forms of oligomers, while evidence in the literature points to soluble aggregate forms being more toxic than insoluble aggregates (Karpinar et al, 2009;Winner et al, 2011;Rockenstein et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, our findings indicate that synapsin III is implicated in α-syn aggregation, although the molecular features of this effect warrant further investigation. To date, α-syn overexpression in transgenic mice has been found to associate with a decrease in synapsin-Ia/b, synapsinIIa/b and complexin-2 levels in whole brain extracts (Nemani et al, 2010), and its aggregation at cortical synapses induces a decrease of synapsin-I levels (Spinelli et al, 2014), but no study has determined whether α-syn is able to modulate synapsin III at present. Here, we have shown that α-syn interacts with and specifically modulates synapsin III in primary midbrain neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue was then rinsed and left in 0.1 M phosphate buffer (PB) at 4°C until serially sectioned through the striatum (equivalent to +1.4 to +0.14 mm from Bregma) (Franklin and Paxinos, 2007) at 60 μm using a vibratome (Leica vibratome, Leica Microsystems). Pre-embed IHC of striatal tissue using DAB (Sigma, St Louis, MO) as the chromophore was performed as previously described (Spinelli et al, 2014) using antibodies against the DA D1 receptor (Sigma, St Louis, MO; polyclonal, 1:100 dilution), DA D2 receptor (Millipore, Burlington, MA; polyclonal, 1:50 dilution), VGLUT1 (Synaptic Systems, Gottingen, Germany; polyclonal 1:1000) and VGLUT2 (Synaptic Systems; polyclonal 1:100). Labeling for each antibody was carried out on separate pieces of striatal tissue, as well as double labeling for either the direct (D1) or indirect (D2) pathways, and VGLUT1 and VGLUT2.…”
Section: Methodsmentioning
confidence: 99%